"La terra de Hochelaga" ou le plan de Ramusio de 1556 - Larouche, Pierre (Cap-aux-Diamants, 1994)
Keywords: Autochtones; Hochelaga; Iroquoiens

Natives and Newcomers: Canada's "Heroic Age" reconsidered - Trigger, Bruce Graham (McGill-Queen's University Press, 1994)
Plusieurs réimpressions
Keywords: Autochtones; Français; Iroquoiens; Iroquois